Metaphorical Translation in Adonis's Janāzatu Imra’atin Poem - Umi Nurun Ni'mah; Tika Fitriyah (Universitas Ahmad Dahlan, 2025)
The research of translating metaphors in poetry holds significance in academia due to its consideration of the resemblances between the source and target languages in poetry translation, encompassing not just semantic meaning but also formal structure. This study is descriptive-qualitative research that aims to categorize the metaphorical expressions within the